Fabrication of GO@MIL-101(Fe) for enhanced visible-light photocatalysis degradation of organophosphorus contaminant. (February 2020) - Lin, Jialing; Hu, Han; Gao, Naiyun; Ye, Jinshao; Chen, Yujia; Ou, Huase
Highlights: GO doping extends the absorption spectrum of MIL-101(Fe) toward long wavelength. GO@MIL-101(Fe)/420 nm/H2 O2 photocatalysis has a high degradation efficiency of TCEP. GO doping enhances the electron transport for photocatalysis. GO@MIL-101(Fe) photocatalysis has a robust performance in water medium. Abstract: Metal–organic frameworks (MOFs) have become one of the most attractive classes of materials due to their versatile features. It is desirable to evaluate the photocatalysis performance of MOFs in aquatic medium. In this study, graphene oxide compositing MIL-101(Fe) (GO@MIL-101(Fe)) was fabricated. Based on this MOF, a light/MOF/H2 O2 photocatalysis system was developed to degrade tris(2-chloroethyl) phosphate (TCEP). GO@MIL-101(Fe) has a lower band gap energy (2.17 eV) than MIL-101(Fe) (2.41 eV), suggesting an expansion of visible light absorption from 520 nm to 570 nm. Under 420 nm irradiation, removal of TCEP under the 15%GO@MIL-101(Fe) photocatalysis system followed pseudo-first-order kinetic with a reaction rate constant at 1.64 × 10 −3 s -1 . Using GO@MIL-101(Fe), a fast activation and electron transfer was achieved due to the high conductibility of GO, resulting in a higher removal efficiency of TCEP (∼95% at 30 min) than using MIL-101(Fe) (∼50%). The basic reaction mechanism involved the excitation of electrons from HOMO (oxygen orbitals in ligands) to LUMO (Fe(II)/Fe(III) in core nodes) induced by visible light irradiation, followed by the electron transport between GO@MIL-101(Fe) and H2 O2 to generate OH. GO@MIL-101(Fe) visible-light photocatalysis would be a potential treatment process for organic contaminants.